2010
DOI: 10.1016/j.solidstatesciences.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of vibrating beam resonators in Quartz, GaPO4, LGS and LGT

Abstract: The present paper reviews and compares the properties of vibrating beam resonators in length-extensional, flexural and cylindrical-torsional modes; resonators are designed and built with new piezoelectric materials: Gallium orthophosphate (GaPO 4 ), Langasite (LGS) and Langatate (LGT). Their characteristics are compared with the results obtained with the same structures built in classical Quartz crystal.For all 3 new crystals, temperature-compensated cuts have been found for length-extensional and flexural mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Douchet designed a vibrating beam resonator with the crystals possessing a 32-point group, and revealed that the crystals with length-stretching vibration mode possessed the zero-frequency cut symbol [ 148 ].…”
Section: Applications Of Piezoelectric Nanomaterials At High Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Douchet designed a vibrating beam resonator with the crystals possessing a 32-point group, and revealed that the crystals with length-stretching vibration mode possessed the zero-frequency cut symbol [ 148 ].…”
Section: Applications Of Piezoelectric Nanomaterials At High Temperaturementioning
confidence: 99%
“…( c ) YCOB-based high-temperature acoustic emission sensor samples (upper panel) and the HSU-Nielsen acoustic emission test setup (bottom panel).Reproduced with permission from Refs. [ 147 , 148 ] Copyright: 2018 American Institute of Physics. ( d ) YCOB-crystal-based high-temperature piezoelectric vibration sensor (upper panel) and high-temperature sensor experimental test equipment (bottom panel).…”
Section: Figurementioning
confidence: 99%